PENGARUH PENERAPAN AKUNTABILITAS KEUANGAN, PEMANFAATAN TEKNOLOGI INFORMASI, KOMPETENSI APARATUR PEMERINTAH DAERAH DAN KETAATAN TERHADAP PERATURAN PERUNDAGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This research want to prove the effect of financial accountability implementation,technology information use, local government official competence and obedience torole of legislation to government performanc accountability, case study of KuantanSingingi Regency. Data was collected by mail. The respondence was thegovernment performance report maker, consist of 62 people. Hypothesis testing isdone by using multiple linear regression analysis with signifince degree 5%. Theresult of this research show that financial accountability implementation (X1) andobedience to role oh legislation (X4) have significant influence to governmentperformance accountability. In otherhand, technology information use (X2) and localgovernment official competence does not have significant influence.Keywoods:Government performance accountability, financial accountability,technology information use, local government official competence,obedidience to role of legislation